2016
DOI: 10.1002/cbf.3224
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR‐221 serves as a biomarker for Parkinson's disease

Abstract: Parkinson's disease (PD) is the common age-related neurodegenerative disorder. Sensitive, noninvasive biomarkers that facilitate PD diagnosis and stage assignment are currently unavailable. This study aims to investigate the potential of 16 previous reported PD-associated miRNAs as novel biomarkers for PD. The expression of 16 serum miRNAs was measured by quantitative reverse transcriptase polymerase chain reaction in 138 PD patients and 112 control populations. Analyses were undertaken to assess the specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 26 publications
5
73
0
2
Order By: Relevance
“…Evaluation of miRNAs in serum of 138 PD patients and 112 controls by qRT-PCR identified 4 candidate miRNAs in PD (miR-29c-3p, miR-146a-5p, miR-214-3p, and miR-221-3p). Among those, miR-221 was found decreased and showed a positive correlation to UPDRS scores and an AUC value of 0.787 for PD-prediction ( Ma et al, 2016 ). Again, all mentioned studies show a very limited overlap in detected target miRNAs and only miR-29c-3p, miR-214-3p, and miR-221-3p were reported in more than one study.…”
Section: Circulating Mirnas As Biomarkers In Parkinson’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of miRNAs in serum of 138 PD patients and 112 controls by qRT-PCR identified 4 candidate miRNAs in PD (miR-29c-3p, miR-146a-5p, miR-214-3p, and miR-221-3p). Among those, miR-221 was found decreased and showed a positive correlation to UPDRS scores and an AUC value of 0.787 for PD-prediction ( Ma et al, 2016 ). Again, all mentioned studies show a very limited overlap in detected target miRNAs and only miR-29c-3p, miR-214-3p, and miR-221-3p were reported in more than one study.…”
Section: Circulating Mirnas As Biomarkers In Parkinson’s Diseasementioning
confidence: 99%
“…Most studies mentioned here performed ROC curve analysis to estimate the diagnostic accuracy of the proposed miRNAs. The diagnostic accuracy for single miRNAs ranged between 63% ( Ma et al, 2016 ) and 97% ( Gui et al, 2015 ) and was improved when multiple miRNAs were combined to a panel (77% ( Botta-Orfila et al, 2014 ) to 99% ( Gui et al, 2015 )). Compared to the average diagnostic accuracy based on clinical criteria, which varies between 73.8% (examination by non-experts) and 83.9% (examination by movement disorder experts after follow-up) ( Rizzo et al, 2016 ), some of the proposed miRNA biomarkers have a higher diagnostic value and discriminated PD cases better from controls than the clinical assessment alone.…”
Section: Circulating Mirnas As Biomarkers In Parkinson’s Diseasementioning
confidence: 99%
“…[15][16][17] Moreover, miR-221 is suggested to be down-regulated and to serve as a potential biomarker for PD. 18 Additionally, miR-221 inhibits cell apoptosis and promotes neuronal survival in PD. 19 Functional lncRNA is known to act as competing endogenous RNA (ceRNA) to sponge miRNA in many conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate whether miR-24 played an important role in rotenone-induced dopaminergic neuron injury, we first investigated its expression in MN9D cells treated with different concentrations of rotenone (10,20,50, and 100 nM). As shown in Figure 2A, miR-24 expression was dose-dependently up-regulated after rotenone treatment, while DJ-1 expression was dose-dependently downregulated.…”
Section: Interfering With Mir-24 Alleviated Rotenone-induced Dopaminementioning
confidence: 99%
“…Recently, growing evidence has revealed that multiple miRNAs are involved in the development of PD. For example, serum miR-221 can act as a PD biomarker [10], and miR-30e can regulate neuroinflammation in PD by targeting Nlrp3 [11]. Moreover, several studies have demonstrated that miRNAs can regulate autophagy in PD.…”
Section: Introductionmentioning
confidence: 99%